A research perspective : preparing pre-service teachers for academic success across South Carolina - Li, Nan, 1960- (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"All educators in teacher education want to know what factors contribute to the academic success of undergraduate education majors or pre-service teachers. Teacher educators of eight universities across the state of South Carolina were determined to find out. The compilation of this book is a result of their inquiry. The conclusions of this book are drawn from the contributors and each chapter helps expand teacher educator readers' understanding and informs their practice as they work with initial certification students in educator preparation. This book promotes the academic success of pre-service teachers by exploring common research questions posed to education majors of the eight universities in South Carolina. Ranging from historically Black to predominately White, from private to public universities across the state, these institutions serve a diverse body of students who described some insightful contributing factors and challenges to their success. The case scenario begins each chapter that provides contextual snapshots of the myriad choices and obstacles faced by pre-service teachers; the research narratives offer insightful analysis for teacher educators. Though written from the perspective of South Carolina, the lessons learned and recommendations for teacher education are relevant to any state"-- Provided by publisher.
Keywords: Education -- Study and teaching (Higher) -- South Carolina.; Teachers colleges -- South Carolina -- Evaluation.; Student teachers -- Rating of -- South Carolina.; Education students -- Rating of -- South Carolina.; Teachers -- Training of -- South Carolina.; Education -- Teacher Training & Certification.; Teacher training.; elektronické knihy; electronic books